Receiving antenna height dependence of radio propagation path loss in fixed wireless access environment - Tan, K. G. (1999)
In Fixed Wireless Access (FWA) applications, the receiving antennas are usually placed at a relatively higher level. The receiving antenna levels from 3 meters up to rooftop level are considered possible in FWA application. This paper shows the variation of radio propagation path loss at different receiving antenna heights. An radio propagation path loss model based on measurement was developed as a function of distance and receiving antenna's height